Development of TUA-WELLNESS screening tool for screening risk of mild cognitive impairment among community-dwelling older adults - Vanoh D (Dove Medical Press, 2016)
Divya Vanoh,1 Suzana Shahar,1 Razali Rosdinom,2 Normah Che Din,3 Hanis Mastura Yahya,4 Azahadi Omar5 1Dietetic Programme, Centre of Healthcare Sciences, Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Kuala Lumpur, Malaysia; 2Department of Psychiatry, University Kebangsaan Medical Centre, Kuala Lumpur, Malaysia; 3Health Psychology Programme, 4Nutrition Programme, Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Kuala Lumpur, Malaysia; 5Institute of Public Health, Ministry of Health, Kuala Lumpur, Malaysia Background and aim: Focus on screening for cognitive impairment has to be given particular importance because of the rising older adult population. Thus, this study aimed to develop and assess a brief screening tool consisting of ten items that can be self-administered by community dwelling older adults (TUA-WELLNESS). Methodology: A total of 1,993 noninstitutionalized respondents aged 60 years and above were selected for this study. The dependent variable was mild cognitive impairment (MCI) assessed using neuropsychological test batteries. The items for the screening tool comprised a wide range of factors that were chosen mainly from the analysis of ordinal logistic regression (OLR) and based on past literature. A suitable cut-off point was developed using receiver operating characteristic analysis. Results: A total of ten items were included in the screening tool. From the ten items, eight were found to be significant by ordinal logistic regression and the remaining two items were part of the tool because they showed strong association with cognitive impairment in previous studies. The area under curve (AUC), sensitivity, and specificity for cut-off 11 were 0.84%, 83.3%, and 73.4%, respectively. Conclusion: TUA-WELLNESS screening tool has been used to screen for major risk factors of MCI among Malaysian older adults. This tool is only suitable for basic MCI risk screening purpose and should not be used for diagnostic purpose. Keywords: mild cognitive impairment, screening, sensitivity, specificity, TUA-WELLNESS